Obesity and the activity of the autonomic nervous system - Colak, Ramis; Dönder, Emir; Karoğlu, Aziz; Ayhan, Oğuz; Yalnız, Mehmet (My University, 2000)
This study was conducted to examine the autonomic nervous system functions of obese people. The study group consisted of 30 healthy obese people (20 female, 10 male, age range 18-58, median 37.6±9.7 years of age) and the control group consisted of 30 healthy nonobese people (18 female, 12 male, age range 17- 56, median 34.4±7.5 years). Each function was tested by non-invasive applications (orthostatic test, isometric exercise test, Valsalva ratio test, 30/15 ratio test, heart rate change test by deep respiration). The results of the orthostatic test and isometric- exercise test yielded a statistically significant difference between the study and control groups. The Valsalva ratio, 30/15 ratio, and heart rate change with deep respiration tests also demonstrated significant differences in the study and in the control group. The results indicate characteristic hypofunctional sympathetic autonomic nervous system dysfunction in obese subjects.
Keywords: Obesity; Exercise Test; Caloric intake; Orthostatic tests; Energy Intake; Autonomic Nervous System